2016
DOI: 10.1002/cctc.201600234
|View full text |Cite
|
Sign up to set email alerts
|

Copper(I)–Phosphinite Complexes in Click Cycloadditions: Three‐Component Reactions and Preparation of 5‐Iodotriazoles

Abstract: The remarkable activity displayed by copper(I)–phosphinite complexes of general formula [CuBr(L)] in two challenging cycloadditions is reported: a) the one‐pot azidonation/cycloaddition of boronic acids, NaN3, and terminal alkynes; b) the cycloaddition of azides and iodoalkynes. These air‐stable catalysts led to very good results in both cases and the expected triazoles could be isolated in pure form under ‘Click‐suitable’ conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…Catalysts Cu­(PPh 3 ) 3 I and CuCl­(IPr), chloro­[1,3-bis­(2,6-diisopropylphenyl)­imidazol-2-ylidene]­copper­(I), were synthesized by known procedures without any modification. Benzyl azide ( 8a ), 1-(azidomethyl)-4-methoxybenzene ( 8b ), 5-(azidomethyl)-1,2,3-trimethoxybenzene ( 8c ), ethyl 2-azidoacetate ( 8d ), 1-(azidomethyl)-4-nitrobenzene ( 8f ), 6-azidohexan-1-ol ( 8g ), 1-azido-4-methoxybenzene ( 8h ), 1-azidohexane ( 8i ), 2,7-dimethylocta-3,5-diyne-2,7-diol ( 1 ), buta-1,3-diyn-1-ylbenzenes ( 4d, 5d ), tri­methyl­( p -tolylbuta-1,3-diyn-1-yl)­silane ( 6a ), ((4-meth­oxy­phenyl)­buta-1,3-diyn-1-yl)­tri­methyl­silane ( 6b ), 6-(trimethylsilyl)­hexa-3,5-diyn-1-ol ( 6c ), trimethyl­(penthyl)­silane ( 6d ), and methoxymethyltrimethylsilane ( 6e ) were synthesized using previously reported procedures.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Catalysts Cu­(PPh 3 ) 3 I and CuCl­(IPr), chloro­[1,3-bis­(2,6-diisopropylphenyl)­imidazol-2-ylidene]­copper­(I), were synthesized by known procedures without any modification. Benzyl azide ( 8a ), 1-(azidomethyl)-4-methoxybenzene ( 8b ), 5-(azidomethyl)-1,2,3-trimethoxybenzene ( 8c ), ethyl 2-azidoacetate ( 8d ), 1-(azidomethyl)-4-nitrobenzene ( 8f ), 6-azidohexan-1-ol ( 8g ), 1-azido-4-methoxybenzene ( 8h ), 1-azidohexane ( 8i ), 2,7-dimethylocta-3,5-diyne-2,7-diol ( 1 ), buta-1,3-diyn-1-ylbenzenes ( 4d, 5d ), tri­methyl­( p -tolylbuta-1,3-diyn-1-yl)­silane ( 6a ), ((4-meth­oxy­phenyl)­buta-1,3-diyn-1-yl)­tri­methyl­silane ( 6b ), 6-(trimethylsilyl)­hexa-3,5-diyn-1-ol ( 6c ), trimethyl­(penthyl)­silane ( 6d ), and methoxymethyltrimethylsilane ( 6e ) were synthesized using previously reported procedures.…”
Section: Methodsmentioning
confidence: 99%
“…Since the discovery, CuAAC has been also expanded for the regioselective synthesis of 5-iodo­(bromo)-1,4-disubstituted 1,2,3-triazoles starting from iodo­(bromo)­alkynes (Scheme A) and 1-substituted 4-ethynyl-1,2,3-triazoles from either terminal diacetylenes or trialkylsilylbuta-1,3-diynes with a one-pot desylilation (Scheme D).…”
Section: Introductionmentioning
confidence: 99%
“…A focused literature survey as regards the choice of arylboronic acids in the synthesis of triazoles revealed that, only a limited number of protocols have earlier been reported . It is worthy to note that, using any of these protocols the synthesis of triazoles has been a two step process.…”
Section: Resultsmentioning
confidence: 99%
“…It was suggested that the phosphinite ligand has better tolerance in terms of functional group and steric hindrance. [ 34 ]…”
Section: Synthesis Of Halotriazolesmentioning
confidence: 99%